Engaging with technological sustainability. Issue 1 (30th November 2021) - Seifi, Shahla
Abstract : Purpose: This study aims to introduce the journal and its purpose. Design/methodology/approach: This study reviews a variety of issues to show the kind of research which is relevant to the journal and the approaches which can be used. Findings: This study shows the great need for research in the ways in which technological development is needed in order to address the issues of sustainability. Practical implications: These can be many and diverse. Originality/value: As the introductory chapter for this new journal its purpose is unique.